The use of personal experience as a strategy for critical reading and writing - Kahu E; Gerrard H (Queensland University of Technology)
Increasingly it is recognised that universities are preparing students for an uncertain future. Accordingly, key graduate attributes of Massey University’s redeveloped Bachelor of Arts degree are critical readin g and writing skills and engaged citizenship. The authors teach two large first-year courses in these topics. Student engagement is critical in these courses because the student cohort is diverse, the courses are compulsory, and the topics are developmental. Some of the assessments have been designed to engage students with the use of personal experience as a strategy for critical reading and writin g. While not without its challenges, this approach has proven to be effective: emotionally engagin g students and enabling them to critically reflect on themselves and the world around them through the development of connected skills and dispositions in critical reading and writing.
Keywords: student engagement; graduate attributes; citizenship; identity; academic literacy